2007 Microsoft Office system inside out - Boyce, Jim 1958-; Pierce, John 1954- (Microsoft Press, 2007)
Provides timesaving tips, tricks, shortcuts, solutions, and troubleshooting guidelines for Microsoft Access, Excel, Outlook, Word, PowerPoint, and other applications and explores new features and capabilities of Office 2007.
Includes index. - Print version record
Keywords: Microsoft Office; Microsoft Access; Microsoft Outlook; Microsoft Excel (Computer file); Microsoft Word; Microsoft PowerPoint (Computer file); BUSINESS & ECONOMICS; Office Automation